2012
DOI: 10.5897/ajb12.1189
|View full text |Cite
|
Sign up to set email alerts
|

First report of papaya meleira virus (PMeV) in Mexico

Abstract: Papaya meleira virus (PMeV), causal agent of meleira or sticky disease, is a double-stranded RNA (dsRNA) virus which has been previously reported only in Brazil. A study was carried out in order to verify the presence and occurrence of PMeV in Mexico. Latex samples from symptomatic and asymptomatic papaya fruits were collected in Quintana Roo state papaya orchards, where the first symptoms of PMeV were observed, and from 29 different municipalities located in ten papaya producer states in Mexico. A molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Soon afterwards, the disease was detected in the states of Pernambuco, Ceara and Rio Grande do Norte (Barbosa et al, 1998a,b). Outside Brazil, Mexico is the only other country where the disease has been reported (Perez-Brito et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soon afterwards, the disease was detected in the states of Pernambuco, Ceara and Rio Grande do Norte (Barbosa et al, 1998a,b). Outside Brazil, Mexico is the only other country where the disease has been reported (Perez-Brito et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Soon afterwards, the disease was detected in the states of Pernambuco, Ceara and Rio Grande do Norte (Barbosa et al, 1998a,b). Outside Brazil, Mexico is the only other country where the disease has been reported (Perez-Brito et al, 2012).The disease's typical symptoms are: excessive exudation of watery latex on the fruit surface, which oxidizes and gives the fruit a stained and sticky aspect; fruit malformation, uneven ripening and changes in the organolepctic properties, rendering it unmarketable.The PMeV genome composition and size are uncommon among plant viruses. PMeV has a double strand RNA (dsRNA) genome, approximately 12 Kb in length, packed into an isometric particle with ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using nuclease treatments, it was shown that the 12-kb band was dsRNA. In addition, the disease was transmitted when the latex from diseased plants was injected into the apex of healthy plants (Perez-Brito et al, 2012). However, attempts to detect PMeV from Mexican orchards using the previously reported C05-3ꞌ primer failed (Araujo et al, 2007; Perez-Brito D, Tapia-Tussell R and Magaña A, personal communication and our own unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only a 669-base pair (bp) sequence encoding a fragment of a putative RNA-dependent RNA polymerase (RdRp) has been reported for this virus (Araújo et al, 2007). Meleira disease was initially described in the early 1980s in Brazil (Kitajima et al, 1993), and was recently detected in Mexican orchards (Perez-Brito et al, 2012). The first symptom is necrosis of the leaf tips, followed by spontaneous exudation of watery-translucent latex in immature fruits.…”
Section: Introductionmentioning
confidence: 99%